Oil Composition of Mengkudu (Morinda Citrofolia L) Seeds - K H Timotius (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2003)
Mengkudu (Morinda citrifolia L.) seeds were macerated or Soxhlet-extracted with various extractants (MeOH, EtAc, Chl : MeOH (2:1, v/v), hexane, and petroleum ether). Fatty acid profile was determined by using GC-MS.The amount of total lipid was varied from 4 - 8 % (w/w) of seed weight depends on the extraction method and the polarity of extractant. The obtained major fatty acids were linoleic acid ( 55-63 % of the total fatty acid methyl esters) followed by oleic acid, palmitic acid, and stearic acid. Chromatography on a silica column with solvent of increasing polarity yielded 85 % neutral lipids, 10 % glycolipids, and 5 % phospholipids. Key words: Oil composition, mengkudu, Morinda citrifolia L., oil seed of noni.